2014
DOI: 10.5194/hess-18-1679-2014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting streamflows in snowmelt-driven watersheds using the flow duration curve method

Abstract: Abstract. Predicting streamflows in snow-fed watersheds in the Western United States is important for water allocation. Since many of these watersheds are heavily regulated through canal networks and reservoirs, predicting expected natural flows and therefore water availability under limited data is always a challenge. This study investigates the applicability of the flow duration curve (FDC) method for predicting natural flows in gauged and regulated snow-fed watersheds. Point snow observations, air temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The abrupt changes in the parameters between two consecutive sub-periods may result in changes in the state variables and fluxes, thereby affecting the simulation results. Hence, all the state variables and fluxes obtained from the different schemes are investigated, and the underlying physical mechanisms are discussed (Kim and Han, 2017).…”
Section: Assessment Of the State Variables And Fluxesmentioning
confidence: 99%
See 3 more Smart Citations
“…The abrupt changes in the parameters between two consecutive sub-periods may result in changes in the state variables and fluxes, thereby affecting the simulation results. Hence, all the state variables and fluxes obtained from the different schemes are investigated, and the underlying physical mechanisms are discussed (Kim and Han, 2017).…”
Section: Assessment Of the State Variables And Fluxesmentioning
confidence: 99%
“…Previous studies have demonstrated that the assumption of time-invariant parameters is usually inappropriate. The reasons are that a unique parameter set optimized by hydrological models only represents the average hydrological processes, which do not accurately represent the dynamic response modes of the catchments processes (Pathiraja et al, 2018;Fowler et al, 2018;Zhao et al, 2017;Kim and Han, 2017;Golmohammadi et al, 2017;Delorit et al, 2017;Chen et al, 2017). To investigate the problems caused by time-invariant parameters, a control scheme, i.e., scheme 1, T. Lan et al: Dynamics of hydrological-model parameters: mechanisms, problems and solutions is designed and assessed in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The input-output consistency can be evaluated using correlation between CPI and observed streamflow as in Westerberg et al (2014) and Kim and Kaluarachchi (2014). The Pearson correlation coefficients between CPI and streamflow data of the 45 catchments had an average of 0.67 with a range of 0.43-0.79, and no outliers were found in the box plot of the correlation coefficients.…”
Section: Preliminary Data Processingmentioning
confidence: 99%